Potent Nonnucleoside Reverse Transcriptase Inhibitors Target HIV-1 Gag-Pol - Figueiredo, Anna (Public Library of Science, 2006)
Nonnucleoside reverse transcriptase inhibitors (NNRTIs) target HIV-1 reverse transcriptase (RT) by binding to a pocket in RT that is close to, but distinct, from the DNA polymerase active site and prevent the synthesis of viral cDNA. NNRTIs, in particular, those that are potent inhibitors of RT polymerase activity, can also act as chemical enhancers of the enzyme's inter-subunit interactions. However, the consequences of this chemical enhancement effect on HIV-1 replication are not understood. Here, we show that the potent NNRTIs efavirenz, TMC120, and TMC125, but not nevirapine or delavirdine, inhibit the late stages of HIV-1 replication. These potent NNRTIs enhanced the intracellular processing of Gag and Gag-Pol polyproteins, and this was associated with a decrease in viral particle production from HIV-1-transfected cells. The increased polyprotein processing is consistent with premature activation of the HIV-1 protease by NNRTI-enhanced Gag-Pol multimerization through the embedded RT sequence. These findings support the view that Gag-Pol multimerization is an important step in viral assembly and demonstrate that regulation of Gag-Pol/Gag-Pol interactions is a novel target for small molecule inhibitors of HIV-1 production. Furthermore, these drugs can serve as useful probes to further understand processes involved in HIV-1 particle assembly and maturation.